A Symbolic Wooden Building in Istanbul: The Amcazade Huseyin Pasha Reception Hall/Divanhane - Erdem, Ayten; Gursel, Ozcan (TRANS TECH PUBLICATIONS LTD, 2013)
The Amcazade Huseyin Pasa. or Koprulu Reception Room / Divanhane ranks as one of the oldest and most important examples of Ottoman house architecture. Located on the shores of the Bosphorus Strait in Istanbul, this building was constructed to house the Austrian ambassador following the Treaty of Karlowitz (1699). The Divanhane is the only surviving part of the summer palace complex built by Grand Vizier Amcazade Huseyin Pasa. It underwent repairs in 1870, 1947, 1954, 1971 and 1978 that were carried out to shore up the structure; however, these modifications also led to the loss of some of the original features of the building. Today, the Divanhane represents a symbol both of Istanbul, and the city's traditional buildings that face the danger of disappearing altogether. This study investigates and documents the special details of this building that are under threat of decomposing.
Keywords: Amcazade; waterfront residence; wood frame; traditional details; Engineering; Materials Science